Influence of proton radiation and strain on nFinFET zero temperature coefficient - Nascimento, Vinicius M.; Agopian, Paula G.D. [UNESP]; Almeida, Luciano M.; Bordallo, Caio C.M.; Simoen, Eddy; Claeys, Cor; Martino, Joao A. (Institute of Electrical and Electronics Engineers (IEEE), 2016)
This paper presents for the first time the study of proton radiation and strain influence on the Zero Temperature Coefficient (ZTC) in SOI nFinFETs based on experimental data and simple analytical model. The strain improves the mobility and consequently the transconductance (gm) and reduces the threshold voltage (VTH) due to the bandgap reduction. Proton radiation degrades gm and decreases VTH mainly for wider fins. We observed experimentally that both parameters (gm and VTH) influence the ZTC bias point, which is also supported by the ZTC analytical model. The VTH influences directly the VZTC in amplitude and the radiation the gm temperature degradation factor (c), consequently leading to undesired changes of VZTC with temperature.
Keywords: FinFET; radiation; SOI; strain; Zero Temperature Coefficient